An estimation of the rates of destruction processes in the Sea of Okhotsk. - Agatova, Alina I; Lapina, N M (PANGAEA, 1996)
An estimate of rate of transformation of organic matter and regeneration of nutrients (in particular phosphorus) was calculated for different regions of the Sea of Okhotsk. The rate was estimated by means of rate of complete oxidation of organic matter to CO2 and H2O catalyzed by enzymes of the electron transport system (ETS) and rate of hydrolytic splitting of phosphate from organic phosphorus compounds catalyzed by alkaline phosphatase. Organic matter destruction rate was at its maximum on the shelf of Kamchatka and Sakhalin, as well as in the layer of maximum oxygen gradients in deep waters. It was found that zones of intensive primary production were characterized by high rates of phosphorus regeneration, which provided for 80% of primary production when concentration of mineral phosphorus was low.
Activity of ETS enzymes and phosphatase in the Sea of Okhotsk and Kuril region in summer 1992 and 1993
Keywords: Akademik A Nesmeyanov; AN_1992; AN_1993; Archive of Ocean Data; ARCOD; GOFLO; Go-Flo bottles; Nesmeyanov-92_2182; Nesmeyanov-92_2185; Nesmeyanov-92_2216; Nesmeyanov-92_2228; Nesmeyanov-92_2229; Nesmeyanov-92_2231; Nesmeyanov-92_2237; Nesmeyanov-92_2361; Nesmeyanov-93_2279; Nesmeyanov-93_2280; Nesmeyanov-93_2292; Nesmeyanov-93_2296; Nesmeyanov-93_2301; Nesmeyanov-93_2305; Nesmeyanov-93_2309; Nesmeyanov-93_2312; Nesmeyanov-93_2313; Nesmeyanov-93_2317; Nesmeyanov-93_2321; Nesmeyanov-93_2356; Nesmeyanov-93_2358; Nesmeyanov-93_2367; Nesmeyanov-93_2370; Nesmeyanov-93_2417; Northwest Pacific; Okhotsk Sea; Sea of Okhotsk